Construction of an alpaca immune antibody library for the selection of nanobodies against Drosophila melanogaster proteins - Qiu, Jianxiang; Li, Jie; Zhang, Zhen; Dong, Shirui; Ling, Xiaomei; Fang, Zhixin; Ling, Quanshou; Huang, Zhixin (Frontiers in Bioengineering and Biotechnology, 2023)
Drosophila melanogaster is a model organism for studying developmental biology and human neural disorders. Nanobodies are the variable domains of the heavy chains of camelid heavy-chain antibodies (VHHs) with high affinity to their antigens and have applications in basic research, similar to traditional antibodies. In addition, nanobodies acting as functionalized antibodies or protein binders have become an additional valuable approach in Drosophila research. In this study, we constructed an immune VHH library against Drosophila embryo proteins with a capacity of 3×107. From this library, nanobodies against three Drosophila proteins, Myc, CyclinE, and CG7544, were enriched and screened by phage display technology and enzyme-linked immunosorbent assay. The most enriched high-affinity nanobodies against Myc, CyclinE, and CG7544 were identified and named A8, N3, and C4, respectively. The DNA sequences of these nanobodies were obtained and then cloned into pADL-10b-Flag-His for expression in Escherichia coli SS320. Purified A8, N3, and C4 were demonstrated to bind corresponding antigens by enzyme-linked immunosorbent assay and surface plasmon resonance in vitro. These nanobodies are ready for further investigation and application in Drosophila research. In summary, we report the availability of an immune VHH library and a highly efficient panning strategy for nanobodies against other proteins in Drosophila.